Effectiveness of Recruitment and Selection in Improving Employee Performance at PNM Mekaar Unit Kadur 2 - Nurul Iman; Nurul Hidayati (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2024)
Recruitment is to provide qualified prospective employees in line with the company’s strategy, insight and values to help reduce the possibility of employee turnover. The recruitment process at PMN Mekaar Unit Kadur 2 pays more attention to the quantity aspect. This can be seen from the fact that prospective employees who register there are accepted easily, because the conditions are easy and the process is short. The focus of this research is the recruitment and selection process in improving employee performance at PNM Mekaar Unit Kadur 2. The objective of this research are to 1) determnine the employee recruitment and selection process, 2) identify obstacles in the recruitment adn selection process, and 3) determine the effectiveness recruitment and selection in improving employee performance at PNM Mekaar Unit Kadur 2. The methot use in this research is qualitative descriptive analysis technique with basic research. For data collection, interview techniques, focus groups, documentation were used. The result of the research show that 1) The stages of the recruitment process include employee request, publication of job vacancies, application process, job interviews and psychological tests, employee selection and field test, and employment contracts. 2) The obstacle faced by the company is that employees easily get discouraged, due to the toxic environment and non compliance with work contracts, and 3) Through the five effectiveness criteria, recruitment and selection are found to be ineffective. Meanwhile, through the six employee perfomance criteriam the recruitment and selection process has a very positive effect on employee performance in the quality, quantity and cost effectiveness indicators and has a negative effect on employee performance in the timelines, need for supervision and interpersonal impact indicators.